PM-3A Nuclear Power Plant Secondary Shield Design - Siler, W C (United States. Government Printing Office., 1961)
"The design, analysis, and selection of system components for functions related to secondary shielding and associated auxiliary systems for the Antarctic PM-3A Nuclear Power Plant are described. Backfill material characteristics, shielding and activation analyses, heat transfer analysis, backfill cooling system, water exclusion and removal system, and instrumentation and control are discussed."